Development of Contextual Material in Aqidah and Akhlak Learning at MTs Baiturrahmah - Siti Fatihah; Alvia Yuliandani; Karenine Aprila; Maryatun; Adi Rosadi (STIT Attaqwa, 2025)
This study aims to describe the implementation of contextual material development in Aqidah Akhlak learning at MTs Baiturrahmah as an effort to improve students’ learning motivation. The background of this research lies in the low motivation and lack of active participation among students in Aqidah Akhlak classes, which negatively impacts discipline and academic achievement. This research employs a qualitative approach using descriptive methods, with data collection techniques including direct observation, in-depth interviews, and documentation of the ongoing learning process. The results indicate that the development of teaching materials directly connected to students’ real-life contexts effectively enhances understanding of religious values, fosters empathy, and increases student engagement and learning enthusiasm. The use of the sociodrama-based learning method also contributes to creating an interactive, enjoyable, and meaningful classroom atmosphere. However, limited classroom time is a major constraint that hinders the comprehensive implementation of this method. Therefore, this study recommends adjusting the allocation of learning time and strengthening contextual learning strategies to improve the overall effectiveness and quality of Aqidah Akhlak instruction in a more holistic and sustainable manner.